Protección jurídica del amazonas: análisis comparado Colombia, Perú, Ecuador y Brasil (2017)
This article is the product of a documentary research, which evidences execution of projects such as: The Petroleum Exploitation in Orito, located in the department of Putumayo in Colombia, The Belo Monte Hydroelectric in Brazil, The Oroya Project in the Republic of Peru and The Ishpingo - Tambococha – Tiputini Project in Ecuador, which are contrary to the current regulations and the precautionary principle, designed to avoid environmental damage, especially when they are irreversible. This allows to visualize the environmental impact facing The Amazon Region and the circumstances that are endangering its conservation, a result of the exploitation of the natural resources that it produces, associated with the climatic changes that affect such a great area thatproduces water and oxygen, essential for the life of man. The Amazon Region includes the countries of Brazil, Ecuador, Peru and Colombia, which within its Constitutional Block have created norms that shelter and protect the natural resources of the exploitations, however, in the light of reality they hardly fulfilltheir mission.